Continuance Intention on Online Shopping A Systematic Literature Review - Emi Amelia; Ade Sobariah Hasanah; Gita Kartika Sari; Yelsha Dwi Pasca (Politeknik Mardira Indonesia, 2025)
This research looks at Continuance intention in online shopping using the systematic literature review method. Continuance intention is an important factor for the company Because related to sustainability business and understand the factors that influence an individual's decision to continue using online shopping services. Survival of a business relies on repeat customer purchases. This research used a systematic literature review with 41 articles selected for reviewed in the period 2016-March 2023. The selected articles were thoroughly reviewed to identify significant variables that influence continuance intention in online shopping, as well as the relationships and influences between these variables. The results of this review show that there are a number of factors that significantly influence continuance intentions in online shopping. Continuance intention focus main that is level strength an individual's intention to make repeat purchases.